6 - Faire face aux conflits d'intérêts économiques dans un monde d'interdépendance: 10.4314/ad.v26i2.22145 - Ngogang , Samuel (Africa Development, 2001)
In this article, the author attempts a study of conflicts as a phenomenon, the concept of economic interests under the constraint of an interdependent world. He argues that there is a conflict of interests every time the choices of people are heterogeneous. The paper focuses on the conflicts of economic interest emanating from the privatisation processes in Cameroon, and which oppose individuals, the society and the state. The author also tries to understand the genesis, process and possible consequences of conflicts of economic interest, by highlighting the role of the state and suggesting ways and means to challenge these consequences.